An Analysis of Domain Mood and Modality of Interpersonal Meaning in Susilo Bambang Yudhoyono (SBY)â€™s Speech - Mustika Amalia; Dedy Subandowo; Eva Faliyanti; Fenny Thresia (Universitas Ahmad Dahlan, 2018)
This research examines the interpersonal meaning in Susilo Bambang Yudhoyono (SBY)â€™s speech. This is based on the details of speech or writing to define an investigation. The object of this research is the used moods and modality types in interpersonal meaning of SBYâ€™s speech under the title â€œToward Harmony among Civilizationsâ€ by Dr.Susilo Bambang Yudhoyono. The aims of this research are (1) to observe the mood and modality types used in SBYâ€™s speech, (2) to observe the dominant mood and modality types in SBYâ€™s speech, (3) to describe the interpersonal meaning in case of mood and modality types in SBYâ€™s speech. The main sources of data in this study are taken from the SBYâ€™s speech at the John F. Kennedy School of Government Harvard University summit on September 29 th, 2009, in Boston, USA. The data then are classified and collected in tabulation. This paper is based on the discourse analysis and systemic functional linguistics approach by Halliday. The writer analyses the speeh by SBY mainly from the interpersonal meaning which focuses on the mood and modality types. The results of this research are (1) there are two mood types in interpersonal meaning of SBYâ€™s speech namely indicative and imperative type, (2) the dominant mood in SBYâ€™s speech is the indicative type which is declarative with the total number of 97 clauses or around 95%, while the dominantly used modality is â€œcanâ€. In addition, the overall dominant modality type exists in median degree modality with the total percentage 40,6%, and (3) the researcher discovers the different mood and modality that might affect the value of the speech to the audience.